New drugs for follicular lymphoma. (October 2016) - Sorigue, Marc; Ribera, Josep-Maria; Motlló, Cristina; Sancho, Juan-Manuel
Highlights: Follicular lymphoma is an incurable disease with a relapsing course. New drugs targeting B-cell antigens and pathways are rapidly becoming available. Results with these drugs are encouraging, particularly in refractory patients. Follow-up is still short and combination regimens remain largely unexplored. Side-effects, including some unusual toxicities, require caution with their use. Abstract: Despite the improvement in prognosis since the advent of rituximab, follicular lymphoma is still incurable and remains the cause of death of most afflicted patients. With the expanding knowledge of the pathogenesis of B-cell malignancies, in the last few years a plethora of new therapies acting through a variety of mechanisms have shown promising results. This review attempts to analyze the evidence available on these new drugs, which include new monoclonal antibodies and immunoconjugates, the anti-angiogenic and immunomodulatory agent lenalidomide, the proteasome inhibitor bortezomib, inhibitors of B-cell receptor pathway enzymes, such as ibrutinib, idelalisib, duvelisib and entospletinib, BCL2 inhibitors and checkpoint inhibitors. We conclude that despite the high expectations around the new therapeutic options for patients with refractory disease, these new drugs have side effects that require caution with their use, particularly in light of the still short follow up and the lack of both randomized trials and data on combination regimens.